1979
DOI: 10.1128/aac.16.3.411
|View full text |Cite
|
Sign up to set email alerts
|

Cinoxacin: pharmacokinetics and tolerance in patients with normal and impaired renal function

Abstract: The pharmacokinetics of cinoxacin, a new antibacterial compound related to nalidixic acid and oxolinic acid, were investigated in 22 patients with varying degrees of renal impairment. After oral administration of cinoxacin at 500 mg every 12 h for 7 days to all patients, the drug was found to be well tolerated. The urine concentrations of cinoxacin in all patients far exceeded the minimal inhibitory concentrations for susceptible organisms commonly found in urinary tract infections. The serum half-life of cino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…Serum and urinary levels, as well as pharmacokinetic parameters of Cinoxacin determined in this study are in agreement with the data reported in the literature (1,2,3, 6,7,13,15,20). For pipemidic acid however we have found a larger percentage of urinary recovery (83% over 24 h) than cited by Humbert et al (12) (63% over 24 h) or Soussy et al (22) (48.3% over 24 h).…”
Section: Discussionsupporting
confidence: 82%
“…Serum and urinary levels, as well as pharmacokinetic parameters of Cinoxacin determined in this study are in agreement with the data reported in the literature (1,2,3, 6,7,13,15,20). For pipemidic acid however we have found a larger percentage of urinary recovery (83% over 24 h) than cited by Humbert et al (12) (63% over 24 h) or Soussy et al (22) (48.3% over 24 h).…”
Section: Discussionsupporting
confidence: 82%
“…This shifting in the time of the peak of the serum levels seems not to affect signifi cantly the height of the peak level which, in our case, is 14.00 ± 3.29 ¡ig/ml after the first administration of cinoxacin, a value comparable to that obtained by other in vestigators [1,2,6], In these elderly patients both the sys temic clearance (1st day 6.55 ± 1.16 liter/h; 7th day 6.38 ± 1.16 liter/h) and the renal clearance (7th day 3.97 ±0.67 li ter/h) are slower than those found in younger people [2,11]. However, the sys temic clearance is found unchanged after multiple administration.…”
Section: Discussionsupporting
confidence: 75%
“…Considering the pharmacokinetic find ings obtained with cinoxacin in aged pa tients and trying to correlate them with the above-mentioned modifications in the pharmacokinetic behaviour of elderly people, a slightly decreased absorption rate may be observed in our patients as the Tmax is reported to be on an average of 2-3 h with a higher absorption rate [1,2,6]. This shifting in the time of the peak of the serum levels seems not to affect signifi cantly the height of the peak level which, in our case, is 14.00 ± 3.29 ¡ig/ml after the first administration of cinoxacin, a value comparable to that obtained by other in vestigators [1,2,6], In these elderly patients both the sys temic clearance (1st day 6.55 ± 1.16 liter/h; 7th day 6.38 ± 1.16 liter/h) and the renal clearance (7th day 3.97 ±0.67 li ter/h) are slower than those found in younger people [2,11].…”
Section: Discussionmentioning
confidence: 99%
“…nigrum has been shown to increase the bioavailability of drugs such as resveratrol, quercetin, and nevirapine. Potent bioactive drugs in the MDP group that are on the market are shown in Figure . Parkinson’s disease, diabetes, epilepsy, and urinary tract infections are treated with piribedil, berberine, stiripentol, and cinoxacin, respectively. From the reported structure–activity relationship studies, chemical linking of the MDP group to the parent structure appeared to enhance the bioactivity. This is probably due to nucleophilic oxygen in the diether group which readily donates electrons to the electrophilic center for interacting with protein residues within the active site to facilitate biological interactions.…”
Section: Introductionmentioning
confidence: 99%